Personalization of parliamentary behaviour: Conceptualization and empirical evidence from Belgium (1995–2014). (March 2021) - Wauters, Bram; Bouteca, Nicolas; de Vet, Benjamin
Personalization of parliamentary behaviour is an underexposed aspect of the broader personalization phenomenon. It is the aim of this article to first clarify the concept of personalization in the parliamentary arena, followed by a systematic investigation of the extent to which and under which circumstances this phenomenon takes place in the Belgian context. We develop four indicators that can be used to measure parliamentary personalization over time and across countries: a rise in the use of individual parliamentary instruments, an increase in single-authored initiatives for activities that could also be conducted collectively, a larger concentration of visible parliamentary activities and an increase in party switching. Our analysis based on an original data set of parliamentary activity in the Belgian House of Representatives (1995–2014) reveals that for none of these indicators a trend of personalization could be noted.